2011
DOI: 10.1111/j.1365-2133.2011.10629.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal changes in menopause: do they contribute to a ‘midlife hair crisis’ in women?

Abstract: Female pattern hair loss is a common problem affecting a large number of women worldwide but beset by a paucity of research. The study of androgens has hitherto dominated the field of hair biology but there is increasing scientific and clinical data to suggest that nonandrogen signals can also affect the folliculosebaceous unit, especially in women. The discovery of oestrogen receptor beta has renewed and redefined prior concepts of oestrogen activity and signalling in hair biology. It is postulated that oestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 37 publications
(76 reference statements)
1
41
0
1
Order By: Relevance
“…14 Conversely, lower systemic estrogen levels have been implicated in the increase of FPHL after menopause. 15 FPHL has been correlated with low systemic estrogen levels when aromatase inhibitors are used in cancer therapy. Topical estrogen preparations are used to treat FPHL in some countries, but their efficacy is questionable.…”
Section: Pathogenesismentioning
confidence: 99%
“…14 Conversely, lower systemic estrogen levels have been implicated in the increase of FPHL after menopause. 15 FPHL has been correlated with low systemic estrogen levels when aromatase inhibitors are used in cancer therapy. Topical estrogen preparations are used to treat FPHL in some countries, but their efficacy is questionable.…”
Section: Pathogenesismentioning
confidence: 99%
“…Microscopic evaluation in FPHL shows patterns that mimic MPA with progressive follicular miniaturization and decreased anagen phase. 13,14,15 Some women with hair loss may present more similarly to the classical male patterns of hair loss. It is reported that 40% of women have FPHL by age 70.…”
Section: (A)mentioning
confidence: 99%
“…There is not a clearly defined division between the more mild findings of normal aging and the more pronounced findings of FPHL. 6,8 When evaluating women complaining of hair thinning, it is important to remember that decreases in hair density are often not publicly perceived until the density has decreased by half. The anagen phase, or growth phase, is the longest phase of the hair cycle.…”
Section: Physiological Hair Changes In Womenmentioning
confidence: 99%
“…6 A schematic of normal hair cycling is presented in Figure 2. 6,8 These changes of decreased hair density and hair diameter lead to physiological hair thinning in all aging women. Following anagen is a short regression phase termed catagen, during which the hair follicle regresses via apoptosis.…”
Section: Physiological Hair Changes In Womenmentioning
confidence: 99%